Flexural strengths and porosities of coated or uncoated, high powder-liquid and resin-modified glass ionomer cements - Nathamon Thongbai-on; Danuchit Banomyong (Elsevier, 2020)
Background/purpose: No study has previously investigated and compared whether resin coating could prevent the effect of dehydration on flexural strengths and porosities of high powder-liquid and resin-modified glass ionomer cements (HPL-GIC and RM-GIC). The purpose of this study is to investigate the effect of resin coating on flexural strengths and porosities of HPL-GIC and RM-GIC under a dry condition. Materials and methods: HPL-GIC (Equia Forte Fil) or RM-GIC (Fuji II LC) was mixed and loaded into a mold to create a bar-shaped specimen, n = 12 of each. The specimens were randomly divided into two groups, coated and uncoated, n = 6 of each. In the coated group, a resin coating agent (Equia Forte Coat) was applied and light cured for 20 s. After 72 h, each specimen was dried and scanned to detect porosities (% volume) using micro-computed tomography. After scanning, flexural strength (MPa) of the specimen was tested using a three-point bending method. Results: Porosities of HPL-GIC were significantly higher than RM-GIC, either coated or uncoated group (p < .05). Flexural strengths of coated and uncoated HPL-GIC were 41.47 ± 0.89 and 15.32 ± 1.15 MPa that were significantly lower than those of RM-GIC at 104.77 ± 3.97 and 52.90 ± 2.17 MPa (p < .05). Flexural strengths of coated GICs were significantly higher than uncoated GICs (p < .05). Conclusion: Resin coating increased flexural strengths of GICs under dry condition. HPL-GIC had higher porosities and lower flexural strength than RM- GIC.